Could the Next Platform be the Transformational Platform and Tourism? A Platform Based Expansion Model in the Context of Global Sustainable Tourism - Zeki Akıncı; Gülseren Yurcu; Ayşe Himmetoğlu; Dilara Bahtiyar Sarı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
After the Second World War, the tourism industry started to turn into a global phenomenon with the development of the economy and globalization since 1950. The restoration of peace and stability in most of the post-war world, emergence of a strong middle class as a result of global financing and economic support, increased tendency to travel, use of idle large-capacity warplanes for civilian purposes are among the important factors ensuring the development and expansion of tourism. Moreover, decrease in long-distance transportation and travel costs, as well as technological development made significant contributions to facilitating access to larger markets, wider geographies, and destinations. In terms of sustainable tourism from 1950 to 2020, the global tourism activity, which caused problems due to conscious and / or unconsciously implemented tourism policies, led to an uncontrollable tourism mobility and geographical expansion with an increasing momentum. In the context of sustainable tourism, this model first analyzes the platform-based model and the geographical expansion model separately, and then synthesizes both models as a mixed model. In addition, this model deals with the development and change processes of global tourism, which is affected by positive and negative developments, and proposes a transformational tourism platform model that provides significant contributions to both the demand side (tourists) and the supply side (tourism industry).